The genetic basis of invasive meningococcal disease revealed thorough whole exome sequencing - Bellos,E; Herberg,J; Wright,V; Klobassa,D; Mashbat,M; Rahman,R; Schlapbach,L; Pouw,R; Kuijpers,T; Levin,M; Sancho-Shimizu,V (BioMed Central, 2018)
BackgroundInvasive meningococcal disease (IMD) is a rare condition affectingchildren and young adults due to infection with Neisseria meningitidis, resulting in meningitis or sepsis. Although the majority of thegeneral population is colonized by N. meningitidis, only a small minority go on to develop IMD, suggesting that those that succumb toinvasive disease may possess an underlying genetic susceptibility.The notion of a genetic contribution to disease manifestation is supported by the finding that patients with congenital complement deficiencies are susceptible to recurrent IMD, yet these conditions arerare. With the aim of identifying other genetic factors underlying IMD, we carried out whole exome sequencing (WES) of approximately 300 IMD patients from an extensive and well characterizedcohort of >2,000 childhood IMD patients.Materials and MethodsThe WES analysis focused on rare variants (MAF<0.01) predicted tohave a detrimental effect on protein function. We undertook analysisof seven multiplex families identifying IBD variants. The rest of theindex cases were analysed as a cohort and put through gene andpathway burden tests to identify any genes/pathways that wereenriched in the collection of patients.ResultsThese analyses revealed a number of patients harbouring mutationsin known primary immunodeficiency genes (approx. 10%) as well asa novel configuration of mutations underlying the complementgenes. Furthermore, novel mutations in the coagulation pathway andmucosal immunity genes were identified and functionally confirmed.ConclusionsThe identification of genes involved in IMD through WES has demonstrated the complex genetic architecture of meningococcal immunityrevealed some novel and unexpected genes/pathways that modulatedisease susceptibility and severity. The results from this studyprovide us with a more comprehensive understanding of IMDpathogenesis.